Sünette lider ve özellikleri - Albayrak, Bünyamin (My University, 2006)
Bu araştırmada Sünnette lider ve özellikleri ele alınmıştır. Bu konuyu tercih etmemizin sebebi, liderlik kurumunun insanlık tarihi kadar eski olmasıdır. İlk insan hayatının yeryüzünde var olmasıyla beraber liderlik de ortaya çıkmıştır. Ve tarihe bir göz atarsak, liderlik rolünü güçlü insanlar yürütmüştür. Ayrıca tarihin bazı dönemlerindeyse peygamberler bu rolü üstlenmiştir. Son peygamber olarak gönderilen Hz. Muhammet de hem bir peygamber hem de bir liderdi. Biz O’nun devlet başkanı ve ordu komutanı olarak uyguladığı liderlik özelliklerini tezimize toplamaya çalıştık. Araştırmamızın giriş bölümünde, lider kelimesinin tanımı, lider türleri ve liderin özelliklerinin neler olduğunu inceledik. Birinci bölümde İslam geleneğinde liderlik ve Hz. Muhammed’in Kur’ân da geçen özelliklerine işaret ettik. İkinci bölümde ise Hz. Peygamber’in başkan ve komutanlık sıfatıyla uyguladığı liderlik özelliklerini toparlayıp güncelleştirmeye çalıştık. Bu çalışma bir olduğundan kapsamı geniş tutulmamıştır. Fakat aynı konu bir doktora çalışmasında başkan, komutan, imam ve aile reisi olarak dört başlık altında daha da genişletilebilir.

In this study, leader and the features of leader in the sunnat was examined. The reason of choosing this subject is that, institution of leadership has an old history as old as history of mankind. Because, by the creation of first humanbeing on the earth, leadership occured. And when we have a look to history, leadership role carried on by the powerful people and also in some terms of history, prophets carried on this role. The last prophet Hz. Muhammed is both a prophet and a leader. In our thesis, we tried to gather his features of leadership which he applied both as a president and an army commander. In the introduction part of the study, we examine the meaning of ‘leader’ word, types of leader and features of leader. In the first part, we attracted attention to leadership in the culture of Islam and features of Hz. Muhammed in Quran. In the second part, we gathered information about leadership features which are Hz. Muhammed applied by the name of president and army commander. And we tired to update these features. This study is a master thesis. So that, its content is limitted. But the same subject can be develop and examine under four subtitle as; president, army commander, imam and head of family in a doctorate study.
Keywords: İslam; Sünnet